Organik Gübreler: Sürdürülebilirliğin Temeli - Akay, Ayşen; Tohumcu, Faruk; Seferoğlu, Saime; Yeşilyurt, Sevinç; Sertkahya, Mehmet; Doğan, Kemal; Ortaş, İbrahim; Razzaghı, Somayyeh; Tepecik, Mahmut (2024)
-